MO893: The Prognostic Value of Dysvolemia, Cardiac Biomarkers and Echocardiographic Parameters in Chronic Haemodialysis Patients. (3rd May 2022) - Paunic, Zoran; Dekleva-Manojlovic, Milica; Markovic-Nikolic, Natasa; Dimkovic, Nada
Abstract: BACKGROUND AND AIMS: Hypervolemia is one of the important risk factors for mortality in haemodialysis (HD) patients. The aim of this study is to determine the prognostic significance of volemia determined by bioimpedance spectroscopy (BIS), as well as cardiac biomarkers and echocardiographic (ECHO) measurements. METHOD: A prospective single-centre observational study included 73 (42 m) chronic HD patients. The BIS and cardiac biomarkers were measured before the second weekly HD procedure. In addition, to overcome the problem of possible different pre-HD and post-HD fluid volume levels (`overhydration', OH and post-HD or `dehydration', DH, respectively) on different HD sessions of the week, the concept of Average Weekly hypervolemia (AVOH) or hypovolemia (AVDH) was implemented—the remaining two OH and DH values were calculated from pre-HD and post-HD weights and normal weight as suggested by BIS measurement. ECHO was performed 1 day after aforementioned measurements (i.e. 1 day after HD). RESULTS: During observation period 11 subjects died (15%): seven (64%) directly due to cardiovascular (CV), two due to infective and due to malignant causes. Three-year cumulative survival was significantly lower (by Kaplan–Meier analysis) in those who had: 1) AVOH >13% extracellular fluid (ECV) (survival rate 73% versus 92% ( P  < 0.05); 2) average AVDH> -3% ECV (survival 69% versus 94%; P  < 0.01); 3) value of serum N-terminal prohormone of brain natriuretic peptide (NT-proBNP)> 7350 pg/mL (survival 76% versus 93%; P  < 0.05); 4) troponin T (TnT) value >0.067 ng/mL, (survival rate 68% versus 94%; P  < 0.01). In addition, regarding just CV mortality, left ventricular ejection fraction according to Simpson (LVEF) <40% (survival rate 80% versus 93%; P  < 0.05) and global longitudinal strain (GLS) <–8.5 (survival rate 81% versus 95%, P  < 0.05) were markers of pure survival. CONCLUSION: Determination of volemia by BIS, cardiac biomarkers and echocardiography has prognostic significance in HD patients. Further studies will show how much correction of dysvolemia affects their better survival.